PEMANFAATAN TUMBUHAN LIAR Lindernia crustacea DALAM FITOREMEDIASI TANAH TERCEMAR MERKURI LIMBAH TAMBANG EMAS SKALA KECIL - Riezka Setya Pratiwi; Yulia Nuraini; Eko Handayanto (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2016)
Gold processing tailings in small-scale gold mine in the form of sludge that still contain Hg and various other metal elements are commonly discharged in agricultural land and water bodies. The discharge of the tailings at Sekotong of West has inhibited growth and yield of maize in the area. The purpose of this study was to explore the potential of Lindernia crustacea for phytoremediation of soil contaminated with small-scale gold mine tailings containing mercury. Lindernia crustacea was grown on the mixture of top soil and (70% weight) and 30% (by weight) of amalgamation or cyanidation tailings for 8 weeks. To enhance uptake of mercury, ammonium thiosulphate was added with doses of 4 and 8 g kg-1 to the planting media when the plant reached 6 weeks old. The results showed that the addition of 4 g and 8 g ammonium thiosulphate increased the accumulation of Hg in the plant shoot by 61% and 27 %, respective, compared to the treatment without addition of ligand. The addition of 4 g and 8 g ammonium thiosulphate also increased 15% and 11% accumulation of Hg, respectively, in the plant root compared to the treatment without addition of ligand. Based on BCF, BAF and TR values, it was known that with or without addition of ammonium thiosulphate, Lindernia crustacean is suitable for use in pytostabilization activities